Analisis Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Karyawan Pada PDAM Sragen - Ary Prasetya, Dody; , Dr. Rini Kuswati, S.E., M.Si (2017)
The purpose of this study were: 1) Determine whether emotional intelligence variables have an influence on employee performance; 2) Determine whether spiritual intelligence variable has an influence on employee performance; 3) to find out which of the variables emotional intelligence and spiritual intelligence are the dominant influence on employee performance. The population in this study were all employees of PDAM Sragen. The sampling technique in this research is purposive sampling or sampling based on the considerations and criteria, in order to obtain a sample of 60 respondents. Methods of data analysis using: 1) The validity; 2) Test reliability; 3) Test for normality; 4) Testing multiple linear regression; 4) Test the hypothesis, the t test and F; 6) Test the coefficient of determination. The results of data analysis showed that: 1) Test the validity of the questionnaire is valid; 2) Test reliability, that this research instrument is reliable; 3) Results of normality test, that the data are normally distributed residuals; 4) The results of multiple linear regression test, showing that the regression coefficient of emotional intelligence is the most dominant variable affecting the performance of the employees of the spiritual intelligence variable; 5) The results of hypothesis testing, the results obtained: a) The results of the t test showed that the variables of emotional intelligence and spiritual intelligence individually significant effect on the performance of employees, this is indicated by the significant value of less than 0.05; b) F test results showed that the variables of emotional intelligence and spiritual intelligence jointly significant effect on the performance of employees, this is indicated by the significant value of less than 0.05; 6) The result of determination coefficient obtained figures adjusted-R2 of 0.457 or 45.7% means that the variables of emotional intelligence and spiritual intelligence is able to explain the variation of the variable performance of employees by 45.7% and the remaining 54.3% is influenced by other variables outside the model researched